Biodegradation of Perfluorooctanoic Acid by Pseudomonas Plecoglossicida Strain DD4 (Baghdad Science Journal, 2022)
Organofluorines, as a pollutant, belongs to a group of substances which are very difficult to neutralize. They are part of many products of everyday use and for this reason they pollute the environment in large quantities. Perfluorinated carboxylic acids are entered into the list of the “Stockholm Convention on Persistent Organic Pollutants” in order to minimize the load on the environment by significantly reducing their use, up to their complete rejection. The DD4 strain was isolated from the soil by the enrichment method and identified using 16S rRNA method as Pseudomonas plecoglossicida. It is able to metabolize perfluorooctanoic acid (PFOA) as the only carbon source in Raymond nutrient medium with a concentration of 1000 mg/l with the release of 132 mg/l fluorine ions. In tests conducted on the biological decomposition of perfluorooctanoic acid, it was possible to quantify its residues using tandem LCMS-IT-TOF. The presented results characterize the Pseudomonas plecoglossicida DD4 strain actively utilized PFOA as the sole carbon source, which characterizes it as a candidate for the creation of biological products aimed at the utilization of organofluorine pollutants.